2017
DOI: 10.1002/ccr3.1075
|View full text |Cite
|
Sign up to set email alerts
|

Acute arterial occlusion after total knee arthroplasty: a case report

Abstract: Key Clinical MessagePopliteal artery occlusion after total knee arthroplasty is rare (0.03–0.17%) but can lead to amputation if overlooked. We should carefully assess vascular patency by Doppler ultrasound and ankle brachial pressure index (ABPI) measurement before and after total knee arthroplasty (TKA) operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…After careful search and screening, 36 studies with 47 cases of arterial occlusion after knee arthroplasty in the past 35 years (1984–2018) were included in the analysis (1 from the present study) (Table S1). Demographics, predisposing conditions, perioperative details, arterial occlusion information, and prognosis are shown in Tables .…”
Section: Resultsmentioning
confidence: 99%
“…After careful search and screening, 36 studies with 47 cases of arterial occlusion after knee arthroplasty in the past 35 years (1984–2018) were included in the analysis (1 from the present study) (Table S1). Demographics, predisposing conditions, perioperative details, arterial occlusion information, and prognosis are shown in Tables .…”
Section: Resultsmentioning
confidence: 99%
“…[ 6 ] Inomata et al describe an acute arterial occlusion after bilateral TKAs in an 80-year-old Asian female. [ 7 ] Ohira et al described an acute popliteal thrombus in a 71-year-old male with calcium pyrophosphate dihydrate crystal deposition disease. [ 8 ] Matziolis et al reported popliteal thrombus in a healthy 69-year-old female with a BMI of 35, and a 74-year-old female with a history of DVT in the contralateral leg after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Inomata et al described the risk factors in a patient with an acute popliteal artery thrombus following TKA by utilizing Virchow's triad: intravascular stasis (no motion of lower extremities under spinal anesthesia, tourniquet use), arterial damage (anterior displacement of tibia during surgery), and hypercoagulability (obesity). [ 7 ] Intravascular stasis, secondary to tourniquet use, is a potential cause for clot development. Tourniquet utilization in TKA has been long debated, and although tourniquets provide decreased perioperative blood loss, there is controversy regarding their role in DVT development.…”
Section: Discussionmentioning
confidence: 99%
“…Embolism and arterial insufficiency may develop due to tourniquet effect in patients with vascular disease and atheroma plaque in the superficial artery [8]. It has been shown that during the manipulation of the superficial femoral artery fixed during tourniquet effect, intimal damage may occur [9]. Improper placement of retractors can also cause damage by direct mechanical trauma [10].…”
Section: Intraoperative Complications 21 Vascular Injuriesmentioning
confidence: 99%